Paradigma dan efektivitas Mahasiswa UINSI dalam membantu memajukan desa Bunga Putih - Hudriansyah, Hudriansyah (TAFANI: Jurnal Pengabdian Masyarakat, 2022)
UINSI has developed KKN activities including a series of interdisciplinary integrative activities that are strategically packaged to solve problems completely and carried out with the community by playing the community as an important and main actor and involving other relevant stakeholders. We raised the title of the activity "Paradigm and effectiveness of UINSI students in helping to advance the Bunga Putih village." The mechanism of this activity has five stages, namely determination, implementation, evaluation of implementation, control, and improvement (PPEPP). The results of this KKN activity were able to make Bunga Putih village better and more advanced in the future. Keywords: Paradigm, Effectiveness, Program